-2
$\begingroup$

$$ x^4 - 3x^2 = 1 \le x^4 - 3x^4 + x^4\\ x^4 - 3x^2 = 1 \le -x^4\\ $$ Is $-x^4 = (-x)(-x)(-x)(-x)$ or $-(x^4)$?

$\endgroup$
4
  • 3
    $\begingroup$ It's $-(x^4)$. It makes sense to define order of operations this way; if we wished to write $(-x)^4$, we would almost always write $x^4$. $\endgroup$
    – user764828
    Apr 2, 2020 at 2:03
  • $\begingroup$ Not all software uses the order of operations conventions for unary minus correctly. $\endgroup$ Apr 2, 2020 at 2:12
  • $\begingroup$ I'll take that into account, thank you. $\endgroup$
    – Eric Lin
    Apr 2, 2020 at 2:24
  • $\begingroup$ Also, $a^{b^c}=a^\left(b^c\right)$ $\endgroup$ Sep 30, 2023 at 12:16

1 Answer 1

0
$\begingroup$

$$(-x)^4=x^4$$ Whereas $$-x^4=-(x^4)$$ The appearance of () changes the answer

$\endgroup$
1
  • $\begingroup$ I see, thanks for clarification. It has always confused me. $\endgroup$
    – Eric Lin
    Apr 2, 2020 at 2:09

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .